Fukushima Through the Prism of Chernobyl: How Newspapers in Europe and Russia Used Past Nuclear Accidents. Issue 4 (19th May 2019) - Perko, Tanja; Prezelj, Iztok; Cantone, Marie C.; Oughton, Deborah H.; Tomkiv, Yevgeniya; Gallego, Eduardo
ABSTRACT: This research explores influential factors of using narratives of Chernobyl in media reporting about the Fukushima nuclear accident: radiological consequences, geographical distance from the accident, status of a nuclear energy production, public opinion about nuclear energy and the level of a nuclear accident (INES scale). This study applies a large-scale media content analysis of newspapers articles ( N  = 1340) published in the first two months of the accident in twelve press opinion leaders in Belgium, Italy, Norway, Russia, Slovenia and Spain. The results show that the memory on the Chernobyl nuclear accident appeared in more than in every third article reporting of the present Fukushima nuclear accident despite the fact that Fukushima carried no direct radiological hazard for the newspaper's audience and, a frequent use of narratives is related to negative attitudes towards nuclear energy, a higher risk perception of nuclear power plants and to an active nuclear energy industry in the newspaper's country.